A tale of two countries: A comparison of the aggregate effects of sectoral reallocation in the United States and Germany - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2011)
This paper compares the aggregate effects of sectoral reallocation in the United States and Western Germany using a stochastic volatility model of sectoral employment growth. Reallocative shocks have no effect on the natural rate of unemployment in either country, and there is mild evidence that reallocative shocks are contractionary over the cycle. The overall statistical contribution of such shocks to the cycle, however, is limited. Reallocative shocks do not appear to be to blame for the rise in trend unemployment in Germany in the 1980s or for a possible rise in trend unemployment in the United States following the Great Recession.
Keywords: E24; E32; J24; J62; 330; Sectoral shifts; reallocation; natural rate; unemployment; turbulence; stochastic volatility; Strukturwandel; Allokation; Schock; Sektorale Beschäftigungsstruktur; Beschäftigungseffekt; Natürliche Arbeitslosigkeit; Konjunkturelle Arbeitslosigkeit; Volatilität; Stochastischer Prozess; Schätzung; Vergleich; Deutschland; USA